PENGARUH PROSES EKSTRAKSI BERTEKANAN DALAM PENGAMBILAN LIPID DARI MIKROALGA JENIS NANNOCHLOROPSIS SP. DENGAN PELARUT METANOL - Purwanti, Ani (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2015)
Microalgae is one of the raw material for biodiesel. Recently, microalgae oil is developed as an alternative fuels to substitute fossil fuels. Lipid was extracted from microalgae and then it was used to produce biodiesel. In this study, the development extraction process is the main issues to investigate the optimum condition. In this research, to get the maximum yield of lipid from microalgae the extraction used an autoclave with high pressure. The microalgae used has water content of 5%, 50%, and 80%. Extraction of 20 gram dried microalgae using 200 mL of methanol as a solvent was carried out in an autoclave at various of pressure (25 psi, 45 psi, 65 psi, and 75 psi). The extraction process was varied from 30 minutes up to 120 minutes. The lipid and methanol was separated from microalgae as biomass by filtration, then the mixture was distilled to separate lipid from methanol as a solvent. The extracted lipid was weighted to determine the yield of lipid. The optimum lipid extraction yield (31.02% as mass of lipid/mass of dried microalgae), was obtained under the following extraction conditions: 200 mL methanol/ 20 gram dried microalgae for 120 minutes processing in 45 psi of process pressure.